Vicotrian rural emergency care - a case for advancing nursing practice - Sullivan, E.; Hegney, Desley; Francis, K. (Wiley-Blackwell Publishing Asia, 2012)
The aim of this paper is to profile the emergency care patients seen by a selection of rural health services in Victoria, and show how advancing nursing practice could contribute to a more sustainable model of care. Quantitative patient data extracted from five rural health services across Victoria ranging in size, were analysed using descriptive statistic techniques. Most patients who attended for emergency care did not require urgent or immediate medical attention (70%), many had minor injuries (over 30%) and did not need medicines (57%) but were attended by a doctor either directly or via telephone (over 74%). If emergency care services in rural Victoria are to be sustained in the face of severe medical workforce shortages, registered nurses will need to be enabled through professional development, legislation and organisation policy to manage autonomously a larger proportion of the non-urgent, less complex patients who present to these emergency services.